أهمية جدول التمويل في تحسين الوضعية المالية للمؤسسة - إيمان, محلو; إيناس, قروي; هدى, بن قانة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى تبيان الدور والأهمية البالغة التي يتميز بها جدول التمويل في تحسين الوضعية المالية للمؤسسة الإقتصادية، حيث يدخل ضمن المواضيع الأساسية في الإدارة المالية ويفتح اهتمامات متعددة الأشكال. فهو عبارة عن وثيقة توضح مصادر خلق السيولة والإستعمالات التي وجهت لها هذه الأموال خلال فترة زمنية محددة، كما يوضح التغيرات في ثروة المؤسسة لنفس الفترة. كما يسهل عملية التحليل لمختلف الإستراتيجيات المتخذة من طرف المؤسسة. "this study aims to demonstrat the role and extreme importance of the financing plan in improving the financial situation of the economic institution because it enters among the fundamental subjects of financial management and opens various it's a document explains the sources of cash creation and the uses to which these funds were directed during a specific period of time، explains the changes in business wealth for the same period and facilitates the process of analyzing the different strategies adopted by the institution "
Keywords: جدول التمويل، تحسين الوضعية المالية.; financing schedule، improving the financial position.